Intratumoral Genetic Heterogeneity in Rectal Cancer: Are Single Biopsies representative of the entirety of the tumor?. Issue 1 (January 2017) - Bettoni, Fabiana; Masotti, Cibele; Habr-Gama, Angelita; Correa, Bruna R.; Gama-Rodrigues, Joaquim; Vianna, Maria R.; Vailati, Bruna B.; São Julião, Guilherme P.; Fernandez, Laura M.; Galante, Pedro A.; Camargo, Anamaria A.; Perez, Rodrigo O.
Abstract : Objective: Demonstrate intratumoral genetic heterogeneity in rectal cancer. Background: Several clinical management decisions in rectal cancer may be influenced by pretreatment biopsy information. However, in the setting of significant intratumoral heterogeneity, biopsies may not be representative of the entirety of the tumor and limit the reliability of the information provided from them for clinical decision management. Methods: Three fragments from a single rectal adenocarcinoma were chosen for whole-exome sequencing followed by mutation detection analysis. About 25 Gb of unambiguously mapped sequences were generated for each sample resulting in a median fold-coverage of 35x. Captured sequences mapped to the reference human genome were then used for the detection of somatic point mutations. Results: Overall, 193 unique somatic point mutations were identified. Only 53 (27%) of these were shared by all three fragments, including known genes involved in early phases of the adenoma-carcinoma sequence (such as, APC). Approximately, 115 (59%) mutations were exclusively present in only one of the fragments, including mutations in "driver" genes (DNAH12). Jaccard distances showed a median distance of 0.603 for pair-wise comparison of fragments indicating significant heterogeneity between them. Conclusions: Considerable intratumoral heterogeneity is present among naive rectal cancers. The majority of point mutations detected in different fragments from rectal cancers are frequently unique to a single fragment. These findings support that gene mutations found on single pretreatment biopsies will not necessarily be representative of mutations present in the entirety of the tumor and therefore may limit the utility of the biological information provided by single biopsy fragments for clinical management decisions. Abstract : Supplemental Digital Content is available in the text